Technical efficiency of pineapple production in Republic of Benin - BIAOU, CHABI FÉLIX (My University, 2020)
Assessing the technical efficiency of pineapple producers is essential to avoid waste of resources and above all to target advices for improving the productivity of the pineapple producers. For this, a survey was carried out among 365 randomly selected producers from five major pineapple-producing Communes. Using the meta-border stochastic production model, technical efficiency scores of pineapple producers are estimated. It is found that the average technical efficiency index of pineapple production is 55.92 and 70% of pineapple producers have a technical efficiency index less than 60%. This proves the poor control of pineapple production techniques in Benin and the need to reorganize pineapple production system.
Keywords: Efficiency potential; meta-border stochastic production function; pineapple varieties; technical; efficiency.